Resistance of Food-Maintained Operant Responding to Mechanical Punishment in Rats: Further Evidence for Weak “Affective/Motivational Pain” in Rat Models of Inflammatory and Neuropathic Pain - Negus, S. Stevens; Marsh, S. A.; Townsend, E. A. (Frontiers in Pharmacology, 2021)
Clinically relevant chronic pain is often associated with functional impairment and behavioral depression as an “affective/motivational” sign of pain; however preclinical animal models of inflammatory and neuropathic pain often produce weak evidence of impaired function. We hypothesized that hindpaw mechanical stimulation produced by a requirement to rear on a textured “NOX” plate would punish operant responding in rats treated with intraplantar complete Freund’s adjuvant (CFA, a model of inflammatory pain) or the chemotherapeutic paclitaxel (PTX, a model of neuropathic pain) and produce sustained pain-related depression of operant behavior. Male Sprague-Dawley rats were trained under a progressive-ratio (PR) schedule of food-maintained operant responding, then treated with CFA (100 µl in left hindpaw), PTX (2.0 mg/kg IP on alternate days for 4 total injections; 6.6 mg/kg IV on alternate days for 3 total injections), or saline vehicle. PR break points and mechanical thresholds for paw withdrawal from von Frey filaments were then tracked for 28 days. Subsequently, rats were tested with the opioid receptor antagonist naltrexone to assess latent sensitization and with the kappa opioid receptor (KOR) agonist U69593 to assess KOR function. CFA produced significant mechanical hypersensitivity for 3 weeks but decreased PR breakpoints for only 1 day. Both IP and IV PTX produced mechanical hypersensitivity for at least three weeks; however, only IV PTX decreased PR breakpoints, and this decrease was not alleviated by morphine. After recovery, naltrexone reinstated mechanical hypersensitivity in CFA- but not PTX-treated rats, and it did not reinstate depression of breakpoints in any group. U69593 dose-dependently decreased PR breakpoints in all groups with no difference between control vs. CFA/PTX groups. These results suggest that rearing on a textured NOX plate was not sufficient to punish operant responding in CFA- and PTX-treated rats despite the presence of sustained mechanical hypersensitivity. The rapid recovery of operant responding could not be attributed to latent sensitization, KOR downregulation, or behavioral tolerance. These results extend the range of conditions under which putative chronic pain manipulations produce weak evidence for depression of operant responding as a sign of the “affective/motivational” component of pain in rats.